Acidosis‐induced activation of distal nephron principal cells triggers Gdf15 secretion and adaptive proliferation of intercalated cells. (23rd April 2021) - Cheval, Lydie; Viollet, Benoit; Klein, Christophe; Rafael, Chloé; Figueres, Lucile; Devevre, Estelle; Zadigue, Georges; Azroyan, Anie; Crambert, Gilles; Vogt, Bruno; Doucet, Alain
Abstract: Aim: Type A intercalated cells of the renal collecting duct participate in the maintenance of the acid/base balance through their capacity to adapt proton secretion to homeostatic requirements. We previously showed that increased proton secretion stems in part from the enlargement of the population of proton secreting cells in the outer medullary collecting duct through division of fully differentiated cells, and that this response is triggered by growth/differentiation factor 15. This study aimed at deciphering the mechanism of acid load‐induced secretion of Gdf15 and its mechanism of action. Methods: We developed an original method to evaluate the proliferation of intercalated cells and applied it to genetically modified or pharmacologically treated mice under basal and acid‐loaded conditions. Results: Gdf15 is secreted by principal cells of the collecting duct in response to the stimulation of vasopressin receptors. Vasopressin‐induced production of cAMP triggers activation of AMP‐stimulated kinases and of Na, K‐ATPase, and induction of p53 and Gdf15. Gdf15 action on intercalated cells is mediated by ErbB2 receptors, the activation of which triggers the expression of cyclin d1, of p53 and anti‐proliferative genes, and of Egr1. Conclusion: Acidosis‐induced proliferation of intercalated cells results from a cross talk with principal cells which secrete Gdf15 in response to their stimulation by vasopressin. Thus, vasopressin is a major determinant of the collecting duct cellular homeostasis as it promotes proliferation of intercalated cells under acidosis conditions and of principal cells under normal acid‐base status.